2009
DOI: 10.1038/leu.2009.212
|View full text |Cite
|
Sign up to set email alerts
|

Selective FLT3 inhibitor FI-700 neutralizes Mcl-1 and enhances p53-mediated apoptosis in AML cells with activating mutations of FLT3 through Mcl-1/Noxa axis

Abstract: Treatment using Fms-like tyrosine kinase-3 (FLT3) inhibitors is a promising approach to overcome the dismal prognosis of acute myeloid leukemia (AML) with activating FLT3 mutations. Current trials are combining FLT3 inhibitors with p53-activating conventional chemotherapy. The mechanisms of cytotoxicity of FLT3 inhibitors are poorly understood. We investigated the interaction of FLT3 and p53 pathways after their simultaneous blockade using the selective FLT3 inhibitor FI-700 and the MDM2 inhibitor Nutlin-3 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Our studies also provide an additional, albeit incomplete, rationale for combination-targeted therapy in AML with primary resistance to MDM2 inhibitors in an attempt to overcome resistance. 47 Conversely, our novel finding of an association of mutated Flt3 (Flt-ITD) and heightened sensitivity to MDM2 inhibitors was not expected based on published findings 48 and may be important to AML therapy as: (1) Flt3-ITD AML cases tend to have short remission durations, (2) therapeutic blockage of Flt3 using Flt3 inhibitor monotherapy has not yet resulted in substantial clinical benefits to patients, and (3) application of MDM2 inhibitors to AML with mutated Flt3 and intact p53 may offer clinical benefits. 49 This novel description of a genomic biomarker for MDM2 inhibitor sensitivity thus introduces the concept of "MDM2 inhibitor sensitizer gene mutations" and justifies ongoing searches for additional genes with similar effects.…”
Section: Discussionmentioning
confidence: 53%
“…Our studies also provide an additional, albeit incomplete, rationale for combination-targeted therapy in AML with primary resistance to MDM2 inhibitors in an attempt to overcome resistance. 47 Conversely, our novel finding of an association of mutated Flt3 (Flt-ITD) and heightened sensitivity to MDM2 inhibitors was not expected based on published findings 48 and may be important to AML therapy as: (1) Flt3-ITD AML cases tend to have short remission durations, (2) therapeutic blockage of Flt3 using Flt3 inhibitor monotherapy has not yet resulted in substantial clinical benefits to patients, and (3) application of MDM2 inhibitors to AML with mutated Flt3 and intact p53 may offer clinical benefits. 49 This novel description of a genomic biomarker for MDM2 inhibitor sensitivity thus introduces the concept of "MDM2 inhibitor sensitizer gene mutations" and justifies ongoing searches for additional genes with similar effects.…”
Section: Discussionmentioning
confidence: 53%
“…Combination of sorafenib with the Bcl-2 inhibitor ABT-737 has shown synergistic activity 32 and the new FLT3-ITD inhibitor Fl-700 was shown to also neutralize Mcl-1, a major anti-apoptotic protein. 33 Combinations with chemotherapy may be particularly dependent on the schedule of administration, at least for some of the FLT3 inhibitors. 34,35 Studies of sorafenib in combination with chemotherapy for patients with AML have been initiated and early reports suggest high response rate in patients with FLT3-ITD.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, a ChIPqPCR assay confirmed that all of the RUNX family members could bind to their respective binding sites (Supplemental Fig-11NR cells. MV4-11NR cells bearing an R248W point mutation in p53 were derived from their parental MV4-11 cells (27). Since nutlin-3 treatment did not induce expression of the p53 target p21 in these AML cells (Supplemental Figure 6A), it suggests that the cell cycle regulatory function of wild-type p53 is diminished.…”
Section: Runx1 Depletion-mediated Antileukemic Effect Requires Functimentioning
confidence: 99%